2013
DOI: 10.1007/s12011-012-9597-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between 5-Aminosalicylic Acid (5-ASA) and Para-Aminosalicylic Acid (4-PAS) as Potential Protectors Against Mn-Induced Neurotoxicity

Abstract: Manganese (Mn) is an essential metal for biological systems, however occupational or clinical exposure to high levels of Mn can produce a neurological disorder called manganism. Oxidative stress and neuroinflammation play major roles in the Mn-induced neurodegeneration leading to dysfunction of the basal ganglia. We investigated the toxic effects of MnCl2in an immortalized rat brain endothelial cell line (RBE4) and the protective effects of the radical scavenging aminosalicylic acids, 5-aminosalicylic acid (5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…PAS has been proven to be an effective agent for the treatment of Mn-induced neurotoxicity in brain cells [20] , in experimental animals [13,16,18,19] , and in humans [11,12,14,15,17] . However, the mechanisms by which PAS and its metabolite AcPAS are transported across the BBB remained unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAS has been proven to be an effective agent for the treatment of Mn-induced neurotoxicity in brain cells [20] , in experimental animals [13,16,18,19] , and in humans [11,12,14,15,17] . However, the mechanisms by which PAS and its metabolite AcPAS are transported across the BBB remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has also been provided regarding the effective removal of Mn from the CSF and brain tissues in rats following PAS treatment [18] . More recently, Santos and colleagues reported that PAS is effective in reducing brain Mn burden [19,20] . The authors further suggest that in addition to its role in metal chelation, the anti-inflammatory property of PAS allows it to reduce the level of prostaglandin E 2 (PGE 2 ), which is crucial for the development of neuroinflammation [19] .…”
Section: Introductionmentioning
confidence: 99%
“…Thus efflux of Mn by this transporter would seem to be very effective however more research needs to be done if such therapy will prove beneficial [20]. Similarly, synthetic compounds like ibuprofen, 5 aminosalicylic acids, and para-aminosalicylic acid were shown to protect against mitochondrial damage and apoptosis in vivo and invitro [47,48]. Recently raloxifene, a selective estrogen receptor modulator (SERM) enhanced the expression of Glutamate Aspartate Transporter (GLAST) and glutamate transporter (GLT 1) which take up most of the glutamate from the synaptic cleft to prevent excitotoxic neuronal death.…”
Section: Conventional Approachmentioning
confidence: 99%
“…Of note, anti-inflammatory agents have been reported to decrease Mn neurotoxicity in vitro and after in vivo exposure. For instance, Santos et al (2013) demonstrated in vitro that 5- aminosalicylic acid (5-ASA) and para-aminosalicylic acid (4-PAS) increased mitochondrial and cell viability following Mn exposure [205]. Ibuprofen, a nonsteroidal anti-inflammatory drug, protected striatal neurons from dendritic atrophy and spine loss in rats treated for 2 weeks with the drug prior to Mn exposure [184].…”
Section: Main Textmentioning
confidence: 99%